A4 paper doesn't stifle creativity - Hohpe, Gregor (O'Reilly Media, Inc., 2024)
The role of software architects is transforming. Architects now need to combine organizational and technical knowledge to effect change in their company. In these videos, author Gregor Hohpe shares real-world advice and hard-learned lessons from actual IT transformations.
Online resource; title from title details screen (O'Reilly, viewed July 1, 2024)
Keywords: Software engineering; Computer architecture; Génie logiciel; Ordinateurs; Architecture; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet